Echoes of "mental crossing" in the middle ages on the examples of joan of arc - Olga Boyko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
In the article we present a study on the analysis of the phenomenon of the voices of Joan of Аrc, by the method of document analysis. The article highlights the concept of altered States of consciousness and their particular course under the influence of religion and the сhurch. Explains the archaic manifestations of the psyche and the concept of the "bicameral mind" by J. Janes. On the example of Joan of Аrc deals with the phenomenon of "mental crossroads", which is a manifestation of exceptionalism of one person creates tension in society, which necessarily leads to his psychological growth.